The Environmental and Economic Impacts of the Use of Recycled Asphalt During the Preventive Maintenance of Roadways in the UAE - Al Shehhi, Aishah H. O. (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)